2003
DOI: 10.1175//2560.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Conformal Mappings Used in Limited-Area Models of Numerical Weather Prediction

Abstract: Conformal separable projections from a sphere onto a plane are introduced to generalize the concept of conformal stereographic, conic, and cylindrical projections. The concept of equivalence of projections is used for partition of all considered projections into equivalence classes. The variation coefficient is defined as the ratio between maximum and minimum mesh sizes of numerical grids. The problem of minimization of this coefficient inside each equivalence class is studied. The obtained variation coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…1, the variation coefficient of the classical conformal mappings is plotted as a function of the spherical radius a . The "best" conic and cylindrical mappings were found using the results in [5]. It can be seen that the "best" stereographic mappings assure visibly better uniformity than two others for spherical radius greater than 4000 km.…”
Section: Chebyshev-milnor Theorem If Is a Simply Connected Open Sphementioning
confidence: 96%
See 1 more Smart Citation
“…1, the variation coefficient of the classical conformal mappings is plotted as a function of the spherical radius a . The "best" conic and cylindrical mappings were found using the results in [5]. It can be seen that the "best" stereographic mappings assure visibly better uniformity than two others for spherical radius greater than 4000 km.…”
Section: Chebyshev-milnor Theorem If Is a Simply Connected Open Sphementioning
confidence: 96%
“…In [5,6] it was shown that the variation coefficients of the "best" stereographic, cylindrical and conic mappings satisfy the following inequality: str < cyl < con . Therefore, it is sufficient to minimize the variation coefficient in the class of stereographic mappings in order to find the "best" projection among the classical ones.…”
Section: Minimization Problem For Computational Rectanglementioning
confidence: 99%
“…It was shown in [2], that such cylindrical mapping is tangent to the sphere at the centerpoint P 0 ofΩ γ (that is, P 0 lies on the "new" equator of rotated spherical coordinates) and its distortion coefficient is…”
Section: Distortion Coefficient and Minimization Problemmentioning
confidence: 99%
“…The most used approach is an application of conformal mappings from a sphere onto a plane because these transformations maintain a simple form of the governing equations and also assure local isotropy and smoothness of the variation of physical mesh sizes on computational grid. This way, the problem of the generation of the most uniform mappings appears again (see [2], [3], [8], [15]). …”
Section: Introductionmentioning
confidence: 99%
“…Our aim is to verify through numerical experiments up to what extent the theoretical results presented in [3][4][5] for domains of a specific geometry are applicable in the practical case of the rectangular computational domains. The paper is structured as follows.…”
Section: Introductionmentioning
confidence: 98%